Time Management Implementation in Forming Student Morals at Pesantren Mahasiswa (Pesma) KH Mas Mansur - Amran, Haidar; Azani, Mohammad Zakki (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the implementation of the PESMA Class program and its influence on the discipline of students (Mahasantri) at Pesantren Mahasiswa KH Mas Mansur, Universitas Muhammadiyah Surakarta. Effective organization of time is essential for academic achievement and character development. PESMA KH Mas Mansur upholds a vision to nurture Muhammadiyah cadres who possess sound Islamic beliefs, correct worship practices, noble character, and strong contributions to society goals that are closely aligned with the values of Islamic Religious Education, which emphasize comprehensive personal growth in spiritual, intellectual, and social aspects. Employing a descriptive qualitative method, this research gathers data through interviews, observations, and documentation involving students and PESMA administrators. The findings show that the program helps students establish structured daily routines, cultivate responsibility, and balance both academic and religious commitments. However, challenges such as low motivation, insufficient skills in scheduling, and environmental distractions persist. Therefore, targeted and continuous mentoring is needed to maximize the program’s outcomes.